Alpha and beta adrenoceptors activate interleukin-6 transcription through different pathways in cultured astrocytes from rat spinal cord. (June 2021) - Morimoto, Kohei; Eguchi, Ryota; Kitano, Taisuke; Otsuguro, Ken-ichi
Graphical abstract: Highlights: Noradrenaline increased IL-6 mRNA in cultured astrocytes from rat spinal cord. α- and β-Adrenoceptors were involved in noradrenaline-activated IL-6 transcription. IL-6 mRNA increase by α1 -adrenoceptors was mediated via the PKC/ERK pathway. IL-6 mRNA increase by β-adrenoceptors was mediated via the cAMP/PKA/CREB pathway. Conditioned medium from α2 -agonist-stimulated astrocytes increased IL-6 mRNA. Abstract: In brain astrocytes, noradrenaline (NA) has been shown to up-regulate IL-6 production via β-adrenoceptors (ARs). However, the underlying intracellular mechanisms for this regulation are not clear, and it remains unknown whether α-ARs are involved. In this study, we investigated the AR-mediated regulation of IL-6 mRNA levels in the cultured astrocytes from rat spinal cord. NA, the α1 -agonist phenylephrine, and the β-agonist isoproterenol increased IL-6 mRNA levels. The phenylephrine-induced IL-6 increase was accompanied by an increase in ERK phosphorylation, and these effects were blocked by inhibitors of PKC and ERK. The isoproterenol-induced IL-6 increase was accompanied by an increase in CREB phosphorylation, and these effects were blocked by a PKA inhibitor. Our results indicate that IL-6 increases by α1 - and β-ARs are mediated via the PKC/ERK and cAMP/PKA/CREB pathways, respectively. Moreover, conditioned medium collected from astrocytes treated with the α2 -AR agonist dexmedetomidine, increased IL-6 mRNA in other astrocytes. In this study, we elucidate that α1 - and α2 -ARs, in addition to β-ARs, promote IL-6 transcription through different pathways in spinal cord astrocytes.